Smoking Behavioral Intentions of Nursing Students in Kendari - Deni (Journal of Public Health and Pharmacy)
This study aims to analyze the smoking behavioral intentions of nursing students in Kendari. The type of research used is qualitative with a case study design. The analysis takes the form of domain analysis using Focus Group Discussion data collection techniques for eight nursing students in Kendari. The research results show that smoking behavior is not based on intention. They start smoking by trial and error and are influenced by social friends. The need for an interpersonal communication approach is supported by policies to implement strict and sanctioned no-smoking areas, both on campus and in nursing students' workplaces, to minimize their chances of having the intention to smoke.